Nanostructured Composite Based on Polyaniline and Rice Raw for Removal of Lead(II) and Cadmium(II) from Solution - Thi Binh, Phan; Thi Tot, Pham; Thi Thanh Thuy, Mai; Thi Xuan, Mai; Minh Quy, Bui; The Duyen, Nguyen (Asian Journal of Chemistry, 2013)
Composites based on polyaniline and raw rice were prepared by chemical method from acid medium containing aniline using ammonium persulfate as oxidation agent. The IR-spectrum confirmed the presence of polyaniline existed in composite which having morphological structure in nano scale by SEM and TEM images. Lead(II) and cadmium(II) ion concentrations in solution before and after adsorption process on absorbents were analyzed by atomic absorption spectroscopy. The favourable adsorption process of them was found by dimensionless Langmuir (RL) and Freundich parameter (NF). The maximum adsorption capacity obtained from the Langmuir isotherm model were 217.3913 and 138.8899 mg/g for Pb2+ and Cd2+, respectively. The negative DGº values were found indicating the feasibility and spontaneous nature of the adsorption process for them.